2012
DOI: 10.5402/2012/258769
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Ventricular Late Potentials Detection Using Time-Frequency Representation and Wavelet Denoising

Abstract: This study proposes a method for ventricular late potentials (VLPs) detection using time-frequency representation and wavelet denoising in high-resolution electrocardiography (HRECG). The analysis is performed both with the signal averaged electrocardiography (SAECG) and in real time. A comparison between the temporal and the time-frequency analysis is also reported. In the first analysis the standard parameters QRSd, LAS40, and RMS40 were used; in the second normalized energy in time-frequency domain was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The VLP is a high-frequency and very-low-intensity signal that is localized at the end of QRS duration, and on the beginning part of ST segment [ 34 ], as shown in Fig. 6 .…”
Section: The Ten Potential Ecg Parametersmentioning
confidence: 99%
“…The VLP is a high-frequency and very-low-intensity signal that is localized at the end of QRS duration, and on the beginning part of ST segment [ 34 ], as shown in Fig. 6 .…”
Section: The Ten Potential Ecg Parametersmentioning
confidence: 99%
“…The appearance of VLPs in SAECG may indicate myocardial scar tissue in ventricles leading to delayed ventricular activation 14 . SAECG is being used in identifying the patients with a higher risk of ventricular dysfunction and reentrant ventricular tachyarrhythmia and hence, detecting the patients with a predisposition toward SCD 15 . In a study by Tahara et al 16 the filtered QRS duration was measured in SAECG in patients with ventricular dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…The end of the QRS complex is a particular area of interest, as ventricular late potentials falling outside the standard QRS duration window may represent areas of diseased myocardium and substrate for reentry ventricular tachycardia. These late potentials are commonly visualized using high‐resolution ECGs, where increasing evidence for abnormal signal‐averaged electrograms (SAECGs) can be used as a powerful predictor of worse outcomes in arrhythmia patients (Gadaleta & Giorgio, 2012 ). In relation of electrograms to revascularization procedures, evidence from the Coronary Artery Bypass Graft (CABG) Patch Trial has demonstrated up to two times the mortality rate reported after 2 years post‐surgery in patients with abnormal SAECGs at baseline compared to patients with normal electrocardiograms (Curtis et al., 1997 ; The CABG Patch Trial Investigators & Coordinators, 1993 ).…”
Section: Discussionmentioning
confidence: 99%